FAITH-BASED ARBITRATION EVALUATED: THE POLICY ARGUMENTS FOR AND AGAINST RELIGIOUS ARBITRATION IN AMERICA - Broyde, Michael J. (Journal of law and religion, 2018)
This article explores whether allowing such expansive arbitration is a wise idea for the United States (and other western democracies). Like all arbitration, religious arbitration starts with a contract to arbitrate, but frequently does not invoke the law of the United States as the law to be used to resolve disputes, but instead allows parties to resolve disputes according to their own religious principles, both procedurally and substantively. The article is organized into two substantive parts. One part explores the strengths and weaknesses of the seven arguments against faith-based arbitration, which are (1) one law for one people; (2) religious arbitration produces substantive injustice; (3) religious arbitration produces procedural injustice; (4) religious arbitration is often subtly coercive to its members; (5) liberal society has a difficult time policing religious arbitration; (6) enforcement of religious arbitration sometimes violates people's rights to religious freedom; and (7) allowing religious arbitration promotes isolation and non-integration of religious communities. The next part explains and criticizes the five arguments in favor of religious arbitration, which are (1) religious arbitration is a religious freedom imperative; (2) religious arbitration can resolve some commercial disputes more accurately than secular courts can; (3) religious arbitration is the only way to resolve certain religious problems; (4) secular regulation of religious arbitration helps moderate and integrate religion; and (5) religious arbitration promotes value sharing between religious and secular cultures and as such enriches public discourse. The article concludes with an endorsement of the value of religious arbitration subject to reasonable procedural and substantive limitations.